Interaction Effect of Depth of Cut, Back Rake Angle and Rock Properties on Temperature of Single Polycrystalline Diamond Compact Cutter - Abdullah, A.H. (Materials and Energy Research Center, 2020)
The single polycrystalline diamond compact (PDC) cutterâs performance is affected by temperature during rock cutting process. The study towards understanding the factors and its interaction affecting the cutterâs temperature is essential prior to cutting process optimization. Thus, this study aims to investigate the effect of various cutting parameters and its interaction on the temperature of a single PDC cutter. A series of test was conducted in a lathe machine which utilized facing operation to cut the rock samples at 0.5 to 1.5 mm depth of cut and back rake angle of 5Â° to 15Â°. Two types of rock being tested in this study were Indiana limestone and Carthage marble. The analysis of variance (ANOVA) output indicated that cutting parameters and rock properties and its interaction have a significant effect on cutterâs temperature except for interaction between back rake angle and rock properties. Increasing the depth of cut and decreasing back rake angle has resulted in increasing temperature. The temperature of the single PDC cutter is higher when cutting Carthage marble than Indiana limestone. Combination of low back rake angle and high depth of cut producing maximum temperature. It is also validated that the data developed from the mathematical model having a difference of 5 as compared to the experimental data obtained using similar parameters which indicates that the results are reliable and can be forwarded in the future study. Â© 2020 Materials and Energy Research Center. All rights reserved.